E-flow doppler indices for prediction of benign and malignant ovarian tumors - Theera Tongsong (2018)
Objective: To determine the validity of pulsatility and resistance index of transabdominal Doppler ultrasound (e-flow) in distinguishing between benign and malignant adnexal masses. Methods: A cross-sectional descriptive study was conducted on patients scheduled for elective surgery due to adnexal masses at Maharaj Nakorn Chiang Mai Hospital, Thailand, between April 2006 and March 2008. All patients were sonographically evaluated for pulsatility and resistance indices aided with color e-flow within 24 hours of surgery. The examinations were performed by the same experienced sonographer, who had no information on the patients, to differentiate between benign and malignant adnexal masses based on Doppler indices. The final diagnoses were based on either pathological or operative findings, used as gold standards. Results: Three hundred and twenty-nine patients were recruited and 23 were excluded, since the masses were finally not proven to be adnexal, for example with intrauterine myomas. Of the remaining 306 cases available for analysis, 191 were benign and 115 were malignant. The sensitivity and specificity of the pulsatility index for distinction were 93.0% and 92.7%, respectively and the values for the resistance index were 94.8 % and 93.2%. Conclusions: Pulsatility and resistance indices with transabdominal Doppler ultrasound (e-flow) have high accuracy for differentiating between benign and malignant adnexal masses.